Biological notes on the parasitism of apoica flavissima Van der Vecht (Hymenoptera: Vespidae) by Seminota marginata (Westwood) (Hymenoptera: Trigonalidae): Are social paper wasps primary or secundary hosts of trigonalidae? - Santos, E. F.; Noll, F. B. [UNESP] (Universidade Estadual de Feira de Santana, 2013)
Hosts of Trigonalidae include larvae of social paper wasps, which have been considered secondary hosts, supposedly following predation of the primary host (usually caterpillars) by adult wasps. This study provides observations on biological aspects of the parasitism of Apoica flavissima Van der Vecht by Seminota marginata (Westwood), and suggests that social wasps may be both primary and secondary hosts, whereas they extract and chew vegetable fiber.
Keywords: Epiponini; Facultative host; Neotropical; Polistinae